Upaya Meningkatkan Hasil Belajar Kimia dengan Metode Discovery Melalui Kegiatan Laboratorium Siswa Kelas XI SMA Negeri 2 Baubau Tahun Pelajaran 2018/2019 - La Ode Abdul Al Azhar (Jurnal Akademik FKIP Unidayan, 2019)
This research aims to improve student learning outcomes in chemistry with discovery methods through laboratory activities on the concept of colloidal systems. This research was carried out at SMA Negeri 2 Baubau from September to October 2018. The method used in this study was classroom action research with a sample of 33 students who were taught with the discovery method through laboratory activities. Classroom Action Research conducted consists of two research cycles with stages in each cycle including planning, implementing, observing, and reflecting. The research instruments used were observation sheets, questionnaires, learning achievement tests, and the results of teacher and student interviews. The results of this study indicate that it has reached the criteria that have become the indicator of success as indicated by increasing the category of aspects of active student participation in learning in each cycle. Likewise with the test of learning outcomes an increase in the average value in the first cycle of 68.09 increased to 74.81 and there are no more students who scored less than 60.00. Similarly, the results of student interviews that respond positively to the learning process using discovery methods through laboratory activities. From these results, it can be concluded that learning by using discovery method learning through laboratory activities can improve student chemistry learning outcomes.